(untitled) (Olhar de Professor, 2024)
This study aims to present and analyze the findings of a review of Brazilian research studies on the Pedagogical Residency Program (PRP) based on the experiences of students (residents). The methodology employed is bibliographic, with research conducted in the Brazilian Digital Library of Theses and Dissertations (BDTD), the Catalog of Theses and Dissertations of CAPES, and Google Scholar, covering the period between 2018 and 2023. The focus is on the Pedagogical Residency Program and its contributions to teacher education. The analysis of the results reveals that Pedagogical Residency contributes in various aspects to teacher education, enhancing both theoretical and practical knowledge for teaching practice, fostering the construction of professional identity, and increasing marketability.